2009
DOI: 10.1002/eji.200838610
|View full text |Cite
|
Sign up to set email alerts
|

PolyI:C plus IL‐2 or IL‐12 induce IFN‐γ production by human NK cells via autocrine IFN‐β

Abstract: NK lymphocytes and type I IFN (IFN-a/b) are major actors of the innate anti-viral response that also influence adaptive immune responses. We evaluated type I IFN production by human NK cells in response to polyI:C, a potent type I IFN-inducing TLR3 agonist. PolyI:C plus IL-2/IL-12 induced IFN-b (but not IFN-a) mRNA expression and protein production by highly pure human NK cells and by the human NK cell line NK92. Neutralizing anti-IFNAR1 or anti-IFN-b Ab prevented the production of IFN-c induced by polyI:C plu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0
2

Year Published

2011
2011
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 43 publications
2
33
0
2
Order By: Relevance
“…Although IL-12 is considered important for the induction of IFN-␥, it has been shown previously that IFN-␥ may also be induced by alternative pathways, including type I IFNs and IL-15 [35][36][37]. Notably, we found that Myd88 Ϫ/Ϫ ;Trif Lps2/Lps2 mice up-regulate Ifnb to a substantial extent during septic peritonitis and that IFN-regulated genes as well as IL-15 are induced normally.…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…Although IL-12 is considered important for the induction of IFN-␥, it has been shown previously that IFN-␥ may also be induced by alternative pathways, including type I IFNs and IL-15 [35][36][37]. Notably, we found that Myd88 Ϫ/Ϫ ;Trif Lps2/Lps2 mice up-regulate Ifnb to a substantial extent during septic peritonitis and that IFN-regulated genes as well as IL-15 are induced normally.…”
Section: Discussionsupporting
confidence: 44%
“…5A), and expression of IL-15 was not altered in the absence of MyD88/ TRIF signaling (Fig. 5B), suggesting that these pathways may contribute to IFN-␥ production in septic peritonitis [35][36][37].…”
Section: Ifn Responses During Septic Peritonitis Do Not Require Myd88mentioning
confidence: 92%
“…As expected, poly I : C directly induced the secretion of IFN-, as well as pro-inflammatory cytokine IL-6 and IL-8 by NK cells in a dose-dependent manner without the help of other cytokines [44]. And NK cells showed a up-regulation of CD69 expression and enhanced cytotoxicity targeting K562 tumor cells [44,45]. Similarly, poly I : C also directly activated human NK cell lines, NK92, YTCl2 and YTS, which all had a notable TLR3 expression [43].…”
Section: Tlr Signaling On Nk Cell Activationsupporting
confidence: 68%
“…Similarly, poly I : C also directly activated human NK cell lines, NK92, YTCl2 and YTS, which all had a notable TLR3 expression [43]. Poly I : C stimulation up-regulated the cytotoxic activity of NK cells targeting K562 and 721.221 cell lines, promoted the secretion of IFN- and induced the CXCL10 mRNA without additional cytokines or cell assist [44,45]. Further study proved that the TLR3 stimulation can directly induce the activation of TRIF/TICAM-1-dependent transcription factor IRF-3 and p38 MAPK in these human NK cell lines, and activation of p38 MAPK was essential for the activation of NK cells [43].…”
Section: Tlr Signaling On Nk Cell Activationmentioning
confidence: 99%
“…4B) can also induce NK activity (37). Activated DCs and KCs secrete IL-6, IL-12, and TNF-␣, which stimulate NK (38,39) and NKT (40) cells to produce IFN-␥. In turn, IFN-␥ upregulates NKmediated lysis of HBV-infected cells, enhances the cytokine response of KC, and recruits HBV-specific T cells (41).…”
Section: Discussionmentioning
confidence: 99%